Mapping Storytelling, Cultural Awareness, and English Language Learning: A Bibliometric-Scoping Analysis of Classroom-Oriented Research (Tamaddun, 2025)
Storytelling has long been positioned as a productive pedagogical resource in English language learning because it connects linguistic form, meaning, imagination, and social experience. However, studies on storytelling and cultural awareness in English as a Foreign Language (EFL) classrooms remain conceptually dispersed across language pedagogy, intercultural communicative competence, children's literature, digital storytelling, and bibliometric methodology. This article revises a narrative literature review into a bibliometric-scoping analysis that maps the intellectual foundations, publication phases, and thematic clusters shaping research on storytelling, cultural awareness, and English language learning. Using a curated corpus of peer-reviewed and scholarly works identified through open scholarly search, publisher pages, ERIC, reference chaining, and methodological sources on science mapping, the study applies descriptive bibliometric mapping, manual keyword normalization, co-word interpretation, and thematic synthesis. The analysis shows that the field has developed through four overlapping phases: foundational theories of communicative and intercultural competence, narrative-based language pedagogy, multimodal and digital storytelling, and systematic or bibliometric consolidation. Five major clusters were identified: intercultural communicative competence, narrative pedagogy, literary and picturebook-based EFL learning, digital storytelling and multimodal composition, and bibliometric research design. The findings suggest that storytelling contributes to cultural awareness when classroom practice moves beyond story exposure toward guided comparison, reflective dialogue, learner identity work, and culturally responsive story production. The study offers theoretical, pedagogical, curriculum, and methodological implications for EFL teachers, teacher educators, materials developers, and researchers. It concludes that storytelling should be treated not as a supplementary motivational activity but as a structured intercultural pedagogy capable of integrating language development, empathy, critical cultural reflection, and learner agency.